Innovations In Information Security Management Smart City - Andrzej Żebrowski; Izabela Szkurłat (Communications of International Proceedings, 2021)
The article presents issues related to the smart city. The concept of it was defined and its functioning was characterised. It was emphasised that the creation of an intelligent city is possible by combining the activities of both the public administration and the urban community. Moreover, it was pointed out that an intelligent city is defined as a place where modern information and communication technologies are used, which significantly increases the efficiency of urban infrastructure with all its elements. It was emphasised that the functioning of smart cities depends primarily on the safe functioning of its infrastructure components (e.g. energy, telecommunications, transport). The information security of this type of cities deserves particular attention, because their functioning and development depend on the smooth functioning of the information and IT infrastructure.
Keywords: smart city; terrorism; cyberspace; threats.